Μελέτη σχολικού κτιρίου με καινοτόμα συστήματα σύμμικτων δοκών και αντισεισμικά συστήματα FUSEIS - Γαλανάκης, Νικόλαος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Δομοστατικής. Εργαστήριο Μεταλλικών Κατασκευών, 2016)
The purpose of this diploma thesis is the design and study, of a two-storey building with load-bearing steel.Instead of conventional modes of manufacturing horizontal floors,in this study, innovative composite beams is being used, the so-called deltabeams. These beams are combined with Precast prestressed slabs in order to provide high flexural strength and the ablility to cover large openings with the lowest possible structural height of the floor. For the collection and transport of the horizontal forces acting perpendicular to the fronts of the building to the foundation, system Fuseis1-1 of dogbone type and steel frames with INERD connections are used instead of the usual stiffness systems. These innovative energy dissipation systems are subject of study and experimentation of Institute of Steel Structures of NTUA. The main advantage of system Fuseis and INERD connections over other stiffness systems is that these elements are easily replaceable if they are plastically deformed or damaged after a strong seismic event. The analysis is performed using the computer program Sofistik, and various construction details were attributed for greater clarity by the program AutoCad. Finally, the building was studied in order to meet the requirements of both the elastic and the anelastic analysis for seismic loads .Following this, nonlinear static analysis (push over analysis) was made in order to examine the response of the structure.